ASPECTOS PSICOLÓGICOS DE PACIENTES COM HIV/AIDS E LIPODISTROFIA ATENDIDOS NO HOSPITAL HELIÓPOLIS - Muller, Sandra Maria (2013)
The epidemic of Acquired Immunodeficiency Syndrome (AIDS) is currently a phenomenon of great magnitude and extent in global health. The lipodystrophy syndrome is a change that affects the body self-image and sexuality, increasing the stigma of the disease and causing difficulties in adherence to treatment and social relations. OBJECTIVES: a) describe aspects of the psychodynamics of HIV / AIDS affected and not affected by lipodystrophy, focusing the defense mechanisms used; b) investigate the perception of body image in HIV / AIDS affected and not affected by lipodystrophy syndrome; c) identify similarities and differences in perceptions of body image in HIV / AIDS patients affected by lipodystrophy with those not affected. METHOD: Eight patients were selected by convenience criterion in the outpatient Clinic of Infectious Diseases of Heliopolis Hospital. We used an Interview Guide - designed and developed with specific questions for the target audience, and the Drawing of the Human Figure projective personality test graphic; the analysis of the data, as indicated by the instrumental, aided by reading the contents of clinical-psychological diagnosis. RESULTS: In both groups the data pointed to common characteristics regarding the internal psychodynamics and the perception of body image. Primitive defensive resources were used in most featuring the dysfunction of body image and a rigid egoic control though fragile. It was noticed how much is distressing for these patients deal not only with self-image as well as sexuality. CONCLUSIONS: Monitoring programs for HIV / AIDS should consider how these patients need to be followed in psychotherapy. Health promotion should take into account not only improves the quality of life, but also seek to understand how these women relate and how they exert their sexuality.